Performance of thermoplastic sugar palm starch biopolymers - Sahari, J.; Maleque, Md. Abdul; Sapuan, S.M.; Ishak, M.R.; Jumaidin, R. (CRC Press, 2019)
Starch is a natural polymer obtained by the photosynthesis process of plants from the regeneration of carbon dioxide. Starch is not a real polymer, but the presence of a plasticizer (water and glycerol at high temperature). Sugar Palm Biofibers, Biopolymers, & Biocomposites makes starch behave like a synthetic polymer. In the presence of a plasticizer (e.g., water, glycerin, or sorbitol) and shearing action, a starch bio-polymer melts and fluidizes so it can be used in injection molding and extrusion, as in the case of synthetic thermoplastic polymers. Many researchers are interested in investigating starch as a biopolymer because of its unique attributes: it is low-cost, renewable, abundant, and available in different forms based on the raw materials used. Biopolymers such as the ones made from starches are superior to some synthetic polymers in terms of resistance to microbial attack and biodegradation. The sugar palm tree (Arenga pinnata) contains starch in its trunk, which can be a good source of biopolymer. In terms of thermal properties, both starches show similar peak gelatiniza-tion temperatures of approximately 67°C. Meanwhile, SPS shows lower crystallin-ity and swelling power than sago. In terms of gel structure, gel made with SPS was more rigid than gel made with sago starch at a high concentration. However, limited research had been carried out to investigate the potential of SPS in biopolymers.